Nanotechnology-based therapeutic applications: in vitro and in vivo clinical studies for diabetic wound healing. (28th October 2021) - Haque, Sheikh Tanzina; Saha, Subbroto Kumar; Haque, Md. Enamul; Biswas, Nirupam
Abstract : Different nanotechnology-based approaches for treating diabetic wounds. Abstract : Diabetic wounds often indicate chronic complications that are difficult to treat. Unfortunately, existing conventional treatment modalities often cause unpremeditated side effects, given the need to develop alternative therapeutic phenotypes that are safe or have minimal side effects and risks. Nanotechnology-based platforms, including nanotherapeutics, nanoparticles (NPs), nanofibers, nanohydrogels, and nanoscaffolds, have garnered attention for their groundbreaking potential to decipher the biological environment and offer personalized treatment methods for wound healing. These nanotechnology-based platforms can successfully overcome the impediments posed by drug toxicity, existing treatment modalities, and the physiology and complexity of the wound sites. Furthermore, studies have shown that they play an essential role in influencing angiogenesis, collagen production, and extracellular matrix (ECM) synthesis, which are integral in skin repair mechanisms. In this review, we emphasized the importance of various nanotechnology-based platforms for healing diabetic wounds and report on the innovative preclinical and clinical outcomes of different nanotechnology-based platforms. This review also outlined the limitations of existing conventional treatment modalities and summarized the physiology of acute and chronic diabetic wounds.